Illicium anisatum Japanese Anise Tree: FPS-276/FP276, 5/2007 - Gilman, Edward (EDIS, 2007)
This document provides a detailed overview of Illicium anisatum, commonly known as the Japanese anise tree. It describes the plant’s physical characteristics, including its height, leaf color, and flower appearance. The document also outlines the plant’s growing conditions, such as its preference for well-drained, rich soil and moderate drought tolerance. Additionally, it highlights the plant’s uses in landscaping, its non-invasive nature, and its general pest resistance. The document concludes with propagation methods and maintenance tips for optimal growth. Original publication date October 1999.